Tourism and its Contribution to Regional Development: Three Case Studies - Calvin Jones; Max Munday (European Regional Science Association (ERSA), 2001)
Fast growing tourism industries have provided a focus for policymakers and academics concerned with regional and national economic development in periphery areas. General and, in the context of this paper, event tourism, comprise an important development platform for both periphery rural areas facing a bleak future due to depressed agriculture conditions, and for post-industrial and urban areas seeking new industries to replace traditional employment in manufacturing and slow growth service industries. The promotion of tourism and leisure service industries as a regional growth driver, particularly in peripheral regions, may ignore certain underlying industry characteristics. Often tourism features low wages and unskilled labour, lessening income-related demand effects, and, further, militating against the development of a highly skilled workforce. Moreover, external ownership of large tourism concerns, together with an underdeveloped local tourism infrastructure can limit the contribution of new tourism activity to regional growth prospects. This paper compares and contrasts the impacts of three very different cases of tourism development in Wales. The first case is the now well-established annual Brecon Jazz festival in mid-Wales. This internationally renowned event attracts 50,000 visitors per annum to a rural setting which faces increasing difficulties in traditional agricultural activities, and is searching for diversification opportunities. The second case examines the sustainable visitor related impacts of Blaenavon Industrial Landscape, an exceptionally well-preserved industrial heritage site in the South Wales coalfield. The area has recently received World Heritage Site status, and is to undergo significant preservation works and development of visitor facilities in the next few years. The third case examines the 1999 Rugby World Cup. The event was hailed as the world's fourth biggest sporting event and was hosted by Cardiff, the capital of Wales in the autumn of 1999. The local economic effects (forecast in the case of Blaenavon) of each development are examined and compared within the framework of Input-Output tables for Wales, augmented by tourism sector data. The paper examines the very different patterns of visitor spend associated with each case activity, and how far the effects of the activities being promoted square with local economic development needs. Implications for tourism development policy are examined in the context of the research findings. Bibliography: Department for Culture, Media and Sport (1999) "Tomorrow%27s Tourism: A growth Industry for the new Millennium" HMSO Fletcher, J. E. (1989). Input-output analysis and tourism impact studies. Annals of Tourism Research, 16: 514-529 Hill, S. & Roberts, A. (1998) %22Welsh Input-Output Tables for 1995" University of Wales Press National Assembly for Wales (2000) "Objective 1 Single Programming Document: West Wales and the Valleys" HMSO
Keywords: 330